Impact of outdoor air on indoor airborne microbiome under hazy air pollution: A case study in winter Beijing. (August 2021) - Zhou, Feng; Niu, Mutong; Zheng, Yunhao; Sun, Ye; Wu, Yan; Zhu, Tianle; Shen, Fangxia
Abstract: Exposure to indoor airborne microbiomes (bioaerosols) is closely associated with human health. However, knowledge regarding the characteristics of indoor bioaerosols in areas affected by serious ambient air pollution is still limited. In this study, indoor bioaerosols were characterized in winter Beijing via quantitative polymerase chain reaction (qPCR) and amplicon sequencing, and compared to outdoor bioaerosols. Concentrations of indoor bioaerosol were significantly lower than those of the adjacent outdoor bioaerosol, and were not significantly affected by outdoor air pollution. Community structures of indoor bioaerosol were distinct from those of outdoor environment, and were differentially affected by ambient air pollution. Specifically, significant change was observed in indoor fungal community impacted by hazy air pollution, while not in bacteria and archaea. Compared to outdoor air, indoor air was preferentially enriched with fungi (~10%) in winter. Besides, about 40% of the bacteria indoors were likely contributed by outdoor bacteria. The results provide useful information regarding the impact of ambient air pollution on indoor bioaerosols, and furtherly highlight the distinction between indoor and outdoor bioaerosol assemblies. Graphical abstract: Image 1 Highlights: Impact of winter haze pollution on indoor airborne bacteria, fungi and archaea was delineated. The abundance and diversity of indoor bioaerosols were lower than those outdoors. The percentage of fungi in bioaerosols indoors was higher that outdoors. Nearly 40% of indoor bacterial communities were contributed by outdoor air. Ambient haze pollution differentially affected the indoor and outdoor fungal aerosols.